G44(P) Enlisting parents as screeners for development dysplasia of the hip – a review of a self-check guide. (27th April 2015) - Lee, A; Doherty, N; Dodds, R; Davies, N
Abstract : Infants have been screened for developmental hip dysplasia (DDH) since the late 1960's. The recognition of the importance for early identification of the condition has been well documented. However, the changes to the national screening programme in 2008 have reduced the surveillance of DDH following the removal of the 8 month infant hip check, leaving only the 6–8 week hip check as standard. A self-check guide for DDH has been developed to enlist parents as screeners for the condition. The guide highlights common signs used to alert to the possibility of hip dysplasia or dislocation. The guide was distributed out between 2008–2013 through maternity services and Health Centres. The guide provided parents with information on classic signs associated with DDH which they were asked to check for. Of those infants referred to our specialist clinic as a result of parental screening, 73% were "abnormal" of these 33% went on to treatment with splintage. The mean age of these infants was 5.36 months. 20% of positive findings were in infants aged 7 month or over at the time seen. None went on to open surgery. These patients represented between 5 and 10% of our overall group of DDH positive patients. If left undiagnosed, they may have gone on to late presentation of hip dislocation requiring surgery as a child or undiagnosed acetabular dysplasia and possible surgical treatment in relatively early adult life. Therefore we concluded that given the right guidance parents/carers would be ideal screeners to assist in detecting possible later presenting DDH in their baby.